Usability of serum annexin A7 as a biochemical marker of poor outcome and early neurological deterioration after acute primary intracerebral hemorrhage: A prospective cohort study - Wang, Chuan-Liu; Xu, Yan-Wen; Yan, Xin-Jiang; Zhang, Cheng-Liang (Frontiers in Neurology, 2022)
Objective: Annexin A7 (ANXA7), a calcium-dependent phospholipid binding protein, may act to aggravate brain injury. This study aimed to assess the clinical utility of serum ANXA7 as a predictor of severity, early neurologic deterioration (END) and prognosis after intracerebral hemorrhage (ICH). Methods: A total of 126 ICH patients and 126 healthy controls were enrolled. Symptomatic severity was evaluated utilizing National Institutes of Health Stroke Scale (NIHSS) score. Lesion volume of ICH was measured according to ABC/2 method. END was referred to as an increase of 4 or greater points in NIHSS score or death at post-stroke 24 hours. Unfavorable functional outcome was a combination of death and major disability at post-stroke 90 days. Results: There were significantly higher serum ANXA7 levels in patients than in controls (median, 46.5 ng/ml versus 9.7 ng/ml; P<0.001). Independent correlations existed between serum ANXA7 levels and NIHSS score (t=2.581, P=0.011) plus hematoma volume (t=2.683, P=0.008). There was a significant elevation of serum ANXA7 levels, with increase in modified Rankin scale scores (P<0.001). Also, serum ANXA7, which was identified as a categorical variable, independently predicted END and an unfavorable outcome with odds ratio values of 4.230 (95% confidence interval (CI), 1.405-12.734; P=0.010) and 2.843 (95% CI, 1.059-7.633; P=0.038) respectively, as well as efficiently differentiated END (area under curve, 0.781; 95% CI, 0.698-0.849) and an unfavorable outcome (area under curve, 0.776; 95% CI, 0.693-0.846). Conclusion: Serum ANXA7 may represent a useful blood-derived biomarker for assessing severity, END and prognosis of ICH.